Bacterial persistence is an active σ(S) stress response to metabolic flux limitation - Radzikowski, Jakub Leszek (Mol Syst Biol, 2016)
While persisters are a health threat due to their transient antibiotic tolerance, little is known about their phenotype and what actually causes persistence. Using a new method for persister generation and high‐throughput methods, we comprehensively mapped the molecular phenotype of Escherichia coli during the entry and in the state of persistence in nutrient‐rich conditions. The persister proteome is characterized by σ(S)‐mediated stress response and a shift to catabolism, a proteome that starved cells tried to but could not reach due to absence of a carbon and energy source. Metabolism of persisters is geared toward energy production, with depleted metabolite pools. We developed and experimentally verified a model, in which persistence is established through a system‐level feedback: Strong perturbations of metabolic homeostasis cause metabolic fluxes to collapse, prohibiting adjustments toward restoring homeostasis. This vicious cycle is stabilized and modulated by high ppGpp levels, toxin/anti‐toxin systems, and the σ(S)‐mediated stress response. Our system‐level model consistently integrates past findings with our new data, thereby providing an important basis for future research on persisters.